Brain-friendly strategies for the inclusion classroom : insights from a neurologist and classroom teacher - Willis, Judy (Gale virtual reference library., 2007)
Judy Willis draws on her experience as a neurologist and classroom teacher to demonstrate brain research-based strategies that provide developmentally and academically appropriate challenges to suit the needs and goals of students with learning disabilities.